Removal of Total Coliform and TSS for Hospital Wastewater by Optimizing the Role of Typha Angustifolia and Fine Sand-Gravel Media in Horizontal Sub Surface Flow Constructed Wetland - Akhmad, Abdul Gani (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2021)
This study aims to evaluate the performance of a pilot-scale HSSF-CW utilizing Typha angustifolia and fine sand-gravel media in removing total coliform and TSS from hospital wastewater. Three pilot-scale HSSF-CW cells measuring 1.00 x 0.45 x 0.35 m3 were filled with gravel sand media with a diameter of 5 - 8 mm as high as 35 cm with a submerged media depth of 0.30 m. There were three treatments, namely the first cell (CW1) without plants, the second cell (CW2) was planted with a density of 12 Typha angustifolia plants, and the third cell (CW3) was planted with a density of 24 Typha angustifolia plants. The three HSSF-CW cells received the same wastewater load with total coliform and TSS contents of 91000 MPN / 100 mg and 53 mg / L, respectively, with Hydraulic Loading Rates 3,375 m3 per day. Wastewater was recirculated continuously to achieve the equivalent HSSF-CW area requirement. The experimental results show that the performance of CW3 is more efficient than CW1 and CW2 in total coliform and TSS removal for hospital wastewater. The pollutant removal efficiency at CW3 reached 91.76% for total coliform with one day hydraulic retention time and 81.00% for TSS with two days of hydraulic retention time. This study concludes that the HSSF-CW system using sand-gravel media with a diameter of 5 - 8 mm with a submerged media depth of 0.30 m and planted with Typha angustifolia with a tighter spacing proved to be more efficient in removing total coliform and TSS from hospital wastewater.